Analisis Pengaruh Kemiskinan dan Indeks Pembangunan Manusia Terhadap Stunting di 34 Provinsi di Indonesia - Sari, Meilan Anja; Rumbia, Wali Aya; Asizah, Nur (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to analyze the effect of poverty and the human development index (HDI) on stunting in Indonesia. This study is a quantitative descriptive study using secondary data sourced from the Indonesian Nutritional Status Survey Report and the Indonesian Central Statistics Agency. The objects of this study were 34 provinces in Indonesia with observations during 2019 - 2022. The analysis method used was panel data regression analysis with the Fixed Effect Model (FEM) using the Eviews 12 analysis tool. The results of the study showed that there was no effect of poverty on stunting and conversely there was an effect of the Human Development Index (HDI) on stunting in 34 provinces in Indonesia..